2019
DOI: 10.3389/fchem.2019.00494
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated LiODFB Electrolyte for Lithium Metal Batteries

Abstract: Nowadays, lithium (Li) metal batteries arouse widespread concerns due to its ultrahigh specific capacity (3,860 mAh g −1 ). However, the growth of Li dendrites has always limited their industrial development. In this paper, the use of concentrated electrolyte with lithium difluoro(oxalate)borate (LiODFB) salt in 1, 2-dimethoxyethane (DME) enables the good cycling of a Li metal anode at high Coulombic efficiency (up to 98.1%) without dendrite growth. Furthermore, a Li/Li cell can be cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…For instance, other salts such as LiFSI, LiTFSI, and additives such as LiBF 4 and LiDFOB, are typically used in Li metal anodes instead of the more traditional LiPF 6 , and sometimes in solventin-salt conditions. [34,44] Even considering price reduction over larger production scale, the cost of these salts will exceed more than 100% the cost of LiPF 6 according to some projections. [45] Figure 4.…”
Section: Considerations Of Cost and Ease Of Manufacturingmentioning
confidence: 99%
“…For instance, other salts such as LiFSI, LiTFSI, and additives such as LiBF 4 and LiDFOB, are typically used in Li metal anodes instead of the more traditional LiPF 6 , and sometimes in solventin-salt conditions. [34,44] Even considering price reduction over larger production scale, the cost of these salts will exceed more than 100% the cost of LiPF 6 according to some projections. [45] Figure 4.…”
Section: Considerations Of Cost and Ease Of Manufacturingmentioning
confidence: 99%
“…The surface states of recovered NCM811 cathodes did not differ after 1 cycle, however, the elements B and N evidently participated in forming CEI layers of the NCM811 cathode cycled with TEAB (Figures 4 and S6). We also observed that the cycled NCM811 cathode had CEI layers mainly composed of C-N (400.2 eV in N1s) 45 and B-O (192.9 eV in B1s) 46 functional groups, which had arisen from molecular structure of the TEAB additive ( Figure S7). This means that electrochemical oxidation of TEAB participates in the formation of a CEI layer.…”
Section: Resultsmentioning
confidence: 86%
“…Further, carbonate‐based 1 m LiPF 6 in the EC–DEC mixture solution was used as electrolyte in assembled pouch cells, which could be one of the principal reasons for capacity fade. The carbonate electrolyte is not compatible with lithium metal anode, especially in the pouch cell design, as discussed in pioneering reports, whereas it is designed for graphite anodes used in LIBs . Deliberately, lithium bis(fluorosulfonyl) imide with triethyl phosphate/bis(2,2,2‐trifluoroethyl) ether was used as an alternative superior electrolyte instead of carbonate electrolyte to enable prolonged cycles.…”
Section: Resultsmentioning
confidence: 99%